Use of non-Conventional Material to Remove Cu+2 ions from Aqueous Solutions using Chemical Coagulation (Journal of Engineering, 2015)
Coagulation - flocculation are basic chemical engineering method in the treatment of metal-bearing industrial wastewater because it removes colloidal particles, some soluble compounds and very fine solid suspensions initially present in the wastewater by destabilization and formation of flocs. This research was conducted to study the feasibility of using natural coagulant such as okra and mallow and chemical coagulant such as alum for removing Cu and increase the removal efficiency and reduce the turbidity of treated water. Fourier transform Infrared (FTIR) was carried out for okra and mallow before and after coagulant to determine their type of functional groups. Carbonyl and hydroxyl functional groups on the surface of okra and mallow were the major groups responsible for coagulation process. By using alum (conventional coagulants), okra and mallow (as a primary coagulant or in combination with the other two primary coagulants) and by the jar testing, the optimum pH-value and dose of the coagulants were determined. The results indicated that the optimal pH values were 6.7, 8 and 6 for alum, okra and mallow, respectively. Mathematical modeling show significant results (sig.